Challenges in genetic testing - Hanson Pierce, Heather (Henry Stewart Talks, 2021)
Genetic testing, Ethical issues, Clinical scenarios of genetic testing, Lynch Syndrome, Huntington’s Disease, Early-onset familial Alzheimer's disease (EOFAD), Indirect genetic testing, Genetics counselling